Faktor-Faktor Yang Mempengaruhi Auditor Switching Secara Voluntary (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Setyowati, Triyana; , Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2017)
Voluntary auditor switching is a changes of auditor or KAP performed by the client company as voluntarily. This study aimed to obtain empirical evidence about the affect of KAP size, the size of the client company, the audit opinion from previous year, change of management, and financial distress to the voluntary auditor switching on manufacturing companies listed on the Indonesia Stock Exchange. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2015. Sample obtained by the method purposive sampling based on predetermined criteria with 135 samples late. The analytical method used is logistic regression analysis. The result show that the KAP size, the size of the client company, and the audit opinion from previous year has affect on voluntary auditor switching. While, change of management and financial distress doesn't affect on voluntary auditor switching.